“Aplicación móvil para apoyar la utilización del diseño universal para el aprendizaje en la práctica docente” - Molina Noboa, Jorge Farouk (2022)
Higher education institutions must comply with evaluation criteria for accreditation purposes and for this reason, they must show that they are making efforts for inclusive education, which implies resorting to methodologies that allow them to address diversity in the classroom. For this purpose, methodologies such as the Universal Design for Learning (UDL) can be used, which offers principles and guidelines for the attention to this diversity. However, the information is usually dispersed and there is a need to organize it. This in turn leads to the need to be able to organize the diversity of tools that could be used. In view of this situation, DUAcentes is proposed, a tool based on mobile devices that seeks to support learning and use of the SAD. Starting from the